Any-Angle Routing for Redistribution Layers in 2.5D IC Packages - Chung, Min-Hsuan; Chuang, Je-Wei; Chang, Yao-Wen (2023 60th ACM/IEEE Design Automation Conference (DAC), 2023)
Redistribution layers (RDLs) are widely applied for signal transmissions in advanced packages. Traditional redistribution layer (RDL) routers use only 90- and 135-degree turns for routing. With technological advances, routing in RDLs can be any obtuse angle, leading to larger routing solution spaces and shorter total wirelength. This paper proposes the first any-angle routing algorithm in the literature for multiple RDLs. We first give a novel global routing algorithm with accurate routing resource estimation. A multi-net access point adjustment method is then proposed based on dynamic programming and our partial net separation scheme. Finally, we develop an efficient tile routing algorithm to obtain valid routes with fixed access points. Experimental results show that our algorithm can achieve a 15.7% shorter wirelength compared with a traditional RDL router.